2020
DOI: 10.21521/mw.6463
|View full text |Cite
|
Sign up to set email alerts
|

Content of vitamin C in edible tissues of snails obtained in Poland

Abstract: Ascorbic acid (Vit. C) is essential for the proper functioning of the human body. Humans are unable to synthesize vitamin C endogenously, so it must be supplied with food. The available literature does not provide any data on the content of vitamin C in the meat of snails. The aim of the study was therefore to determine and compare its content in the edible parts of snails obtained in Poland. The research material consisted of 30 samples of snail meat (the foot with the collar and a fragment of the coat) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A group of Polish scientists and others approached the study of gastropods as an alternative source of ascorbic acid (vitamin C) [2]. This vitamin is an integral component of the diet and cannot be synthesized in the human body.…”
Section: Discussionmentioning
confidence: 99%
“…A group of Polish scientists and others approached the study of gastropods as an alternative source of ascorbic acid (vitamin C) [2]. This vitamin is an integral component of the diet and cannot be synthesized in the human body.…”
Section: Discussionmentioning
confidence: 99%
“…Human utilisation through value-added nutraceutical, industrial and medical application is one of the best methods for controlling this snail population and its distribution, with applications including the discovery of novel endoglucanase [ 3 ], the use of shell nanoparticles as a greenpoxy biocomposite [ 4 ], and the shell CaCO 3 /CaO as the base material of hydroxyapatite [ 5 , 6 , 7 ]. Gondek et al [ 8 ] also reported that A. fulica meat possesses a high protein content (21%) and high levels of unsaturated fatty acids. The mucus of this giant snail has also been widely used in cosmetic supplements and medical biomaterials [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ] according to several functional mucous components, such as antimicrobial proteins (83.67 kDa achasin [ 10 ], and agglutination-inducing lectin or achatinin [ 11 ]), bioactive peptides (11.45 kDa antibacterial mytimacin-AF [ 16 ] and anticancer peptides [ 17 , 18 ]), allantoin and glycolic acid [ 19 ], and a novel glycosaminoglycan, acharan sulfate, with tumour-suppression activity [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contamination of eggs with bird faeces or soil leads to an elevated risk of microbial contamination of the shells, the most commonly mentioned microorganisms are E. Coli, Salmonella, Streptococcus, Staphylococcus and Yersenia (Jones et al, 2004). Eggs from floor/outdoor systems may have considerably higher levels of bacterial contamination than caged eggs (Gondek et al, 2013).…”
mentioning
confidence: 99%